1999
DOI: 10.1046/j.1469-8137.1999.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and utilization of atmospheric ammonia in three native Poaceae species: leaf conductances, composition of apoplastic solution and interactions with root nitrogen supply

Abstract: The physiological potential for acquisition of atmospheric ammonia (NH $ ) was investigated in three European meadow grasses (Arrhenatherum elatius, Bromus erectus and Brachypodium pinnatum) competing in chalk grasslands. Experiments were carried out with plants cultivated for about three months on a soil-sand mixture at high root nitrogen supply or in nutrient solutions at low root nitrogen supply. Two different root nitrogen regimes were applied to the solution-grown plants : 130 µmol NO $ plant −" wk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 55 publications
1
26
0
2
Order By: Relevance
“…Subsequent studies confirmed the existence of this compensation point and found its value was in the range of 0.5-4 |xg m~3 (0.66-5.28 ppbv) with a median value between 1.5 and 2|j,gm _3 (2-2.64 ppbv) [50][51][52][53][54][55][56]. Distinction can be made [57] between stomatal and canopy compensation points.…”
Section: Mechanism Of Uptake Of Ammonia By Plantsmentioning
confidence: 62%
See 1 more Smart Citation
“…Subsequent studies confirmed the existence of this compensation point and found its value was in the range of 0.5-4 |xg m~3 (0.66-5.28 ppbv) with a median value between 1.5 and 2|j,gm _3 (2-2.64 ppbv) [50][51][52][53][54][55][56]. Distinction can be made [57] between stomatal and canopy compensation points.…”
Section: Mechanism Of Uptake Of Ammonia By Plantsmentioning
confidence: 62%
“…(53)- (55). Using these equilibrium constants and Henry's law constants, they outlined an iterative method to calculate the composition of the aqueous solution and vapor pressure above it for a wide range of ammonia concentrations, ratio of mole-fractions of total C0 2 and total ammonia (R = (C0 2 + C0 3 H -+ CO 2 , -+ NH 2 COO~)/(NH 3 +NHj-|-NH2COO _ )), and temperature.…”
Section: Reactions Of Ammonia With Carbon Dioxidementioning
confidence: 99%
“…1 Primary biochemical processes describing the foliar uptake and assimilation of atmospheric ammonia (NH 3 ), nitric oxide (NO), and nitrogen dioxide (NO 2 ). Adapted from Stulen et al (1998 gaseous NH 3 is strongly controlled by the stomatal aperture (Duyzer et al 1994;Hanstein et al 1999;Gessler et al 2000Gessler et al , 2002. However, as described in ''Uptake mechanisms'', the concentration of NH 4 ?…”
Section: Leaf-level Controlsmentioning
confidence: 99%
“…A common observation of plants under fumigation by reactive N is an increase in at least some aspects of leaf N (Rowland 1986;Rowland et al 1987;Segschneider et al 1995;Hanstein et al 1999;Takahashi et al 2005) and there is some level of correspondence between natural variation in foliar uptake and leaf N contents (Calanni et al 1999;Tomaszewski and Sievering 2007;Sievering et al 2007). Therefore, foliar uptake has the potential to alter the stoichiometry of C and N in plant tissues in opposition to that driven by elevated CO 2 .…”
Section: Herbivorymentioning
confidence: 99%
See 1 more Smart Citation